Persepsi Masyarakat Indonesia Terhadap Peran Apoteker Komunitas Dalam Pelayanan Informasi Obat (PIO) Berdasarkan Wilayah - Narwadan, Fortunata; Soegiantoro, Didiek Hardiyanto; Rawar, Ellsya Angeline (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
The role of community pharmacists in providing drug information is increasingly important to improve the safety of drug use by the public. However, public perceptions of the role of pharmacists may vary between regions. This study aims to analyze the influence of region of residence on the perceptions of Indonesians regarding the role of community pharmacists in Drug Information Services (DIS). The study used a quantitative method with a cross-sectional design through the distribution of an online questionnaire covering six variables: General Awareness (GA), Effectiveness (EFF), Collaboration (COLL), Barriers (BARR), Trustworthiness (TRUST), and Drug Information Service (DIS). Validity testing was conducted using KMO and Bartlett's Test as well as PCA factor analysis, which showed that all items had a KMO value > 0.5 and met the construct validity requirements. Reliability was tested using Cronbach's Alpha, with all variables having a value > 0.7, indicating excellent internal consistency. Chi-Square analysis was used to examine the influence of region, while the relationship between variables was tested using Pearson's correlation. The results showed that region did not affect all perception variables (p > 0.05), indicating that public perception was uniform nationwide. Rank Spearman correlation showed that all variables were significantly related, especially between Barriers and PIO (r = 0.768). It is recommended that pharmacists improve the quality of communication and education to strengthen the implementation of PIO in the community.